1964
DOI: 10.1126/science.143.3608.822
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Authorship Trends in Scientific Papers

Abstract: Since 1946 biomedical writers have shown no marked trend toward multiple authorship; the average number of authors per paper remains steady at about 2.3. This is in strong contrast tothe conclusion of Price from a study of Chemical Abstracts that the chemists' trend toward four or more authors per paper has been during this period, and continues to be, steeply exponential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
6

Year Published

1964
1964
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 2 publications
1
34
0
6
Order By: Relevance
“…Smith was one of the first researchers to observe an increase in the incidence of multiple-authorship has been increasing [58], 4 a trend since confirmed by several other investigators [1][2][3][4]40,42] 5. However, such studies have also shown that the rate of increase in multiple-authorship has varied considerably with subject area [40,61], and in a few cases (e.g., biomedicine [7]) there seems to have been no significant growth.…”
Section: Multiple Authorship and Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith was one of the first researchers to observe an increase in the incidence of multiple-authorship has been increasing [58], 4 a trend since confirmed by several other investigators [1][2][3][4]40,42] 5. However, such studies have also shown that the rate of increase in multiple-authorship has varied considerably with subject area [40,61], and in a few cases (e.g., biomedicine [7]) there seems to have been no significant growth.…”
Section: Multiple Authorship and Collaborationmentioning
confidence: 99%
“…Does collaboration vary with the nature of the 7 In recent years, political factors have become more pronounced with certain funding agencies, in particular the European Commission, requiring researchers to seek collaborative partners before they apply for financial support. Transportation and electronic communication are two other contributing factors which up until now do not appear to have received much attention.…”
Section: Factors Contributing To Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he reported that such studies only provide an 'approximate measure of group efforts' [42][43]. Despite this limitation, many studies have utilized co-authorship as a measure of collaboration [44][45][46][47] and the general consensus is that the growth in multiple-authorship is a proof of increase in collaboration [45][46][47][48][49]. Therefore, the collaboration patterns of top authors of Table II were further examined and it was found that the total number of authors brought out by these top ten researchers is 54 and none of these top authors had any single-author publication (during 2003-2011 in this journal).…”
Section: ) Multi-author Trendsmentioning
confidence: 99%
“…1 In the 1930s, the average number of collaborators on scientific papers was roughly two, and this number remained steady for four decades. 2 Authorship and collaboration have changed dramatically since the 1970s, and growth in multi-authorship has accelerated, driven both by academic reward systems and the ease of collaboration in the Internet age. By 2000, the average number of authors in articles published in high-ranking medical journals was seven.…”
mentioning
confidence: 99%